Interpretasi Asnaf Zakat dalam Konteks Fiqih Kontemporer - Malahayati, Malahayati (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2016)
Some benefits of zakat is as form of faith to Allah, but also it has bigger own contribution in process of building Muslim personality as the community and state member. Beside of that, it also could increase the form of social and solidarity as the relationship soul between the rich and poor level. So it will formed balancing of economic empowerment and falah or winning. Contextual understanding about zakat revenue consisted of eight level which is called 8 asnaf 9 (groups) it caused the purpose of zakat will not achieved, because zakat fund distribution to them just only in kind of charity. Furthermore, for the achievement of zakat purpose and benefits of zakat obligation, so the comprehensive and contextual understanding about eight groups or asnaf of zakat receiver need to be done, so the group which has the right to get the fund of zakat will receive their right. This research has the objective to explained how the interpretation of asnaf zakat in contextual classic and contemporary fiqh and to give a brief explanation about the function of zakat to economic empowerment of Muslim community. In alQur’an, the word of zakat and praying was called as many as 82 times in the sequence of words which is successively, so zakat has it owns position as same as praying and we can find more or less 27 articles that put in line the praying with the obligation of zakat payment. The result of research has shown that the understanding of 8 asnaf (groups) should be studied again universally, where at this time the meaning and concentration to the mustahik zakat in the narrow scopes. Zakat is related with relocation of economic source that can enhance the poor’s level to higher degree. To empower of zakat potential economically it’s mean we think how to take the benefit of zakat as one of economic source which can get the benefit or result, maximum and optimal of consumptive and productive benefits, and also, to solve the poverty problem and economic empowerment of Muslim community also to prevent the happen of wealth concentration from some group of people. In term of economic empowerment of Muslim community and eradication of poverty, so the institutions of zakat have to apply the management of zakat based on the development and empowerment, so the presence of those institutions could be the real helper for mustahiq zakat of zakat receiver.